Association of killer cell immunoglobulin‐like receptors with spontaneous clearance of hepatitis C virus in the Chinese population. Issue 4 (15th February 2018) - Shan, Zhengang; Huang, Jieting; Liao, Qiao; Huang, Ke; Wang, Min; Xu, Ru; Tang, Xi; Zhang, Weiyun; Nelson, Kenrad; Fu, Yongshui; Li, Chengyao; Rong, Xia
Abstract : BACKGROUND: Natural killer (NK) cells are critical components in innate immune response to viral infection. Killer cell immunoglobulin‐like receptors (KIRs) are involved in regulating the balance of activation or inhibitory function of NK cells. However, the association of KIRs with the spontaneous clearance of hepatitis C virus (HCV) remains unclear in the Chinese population. STUDY DESIGN AND METHODS: A total of 407 HCV‐seropositive voluntary blood donors were recruited, including 203 with spontaneous viral clearance and 204 with chronic infection. The presence of KIR genes was detected individually by polymerase chain reaction with sequence‐specific primers. Data of HLA and interleukin‐28B ( IL28B ) genotypes were extracted from our previous study. RESULTS: Our results showed that KIR2DL2, 2DS2, 2DL2/2DL3, and 2DL5A–/2DL5B+ were more frequent in subjects with HCV clearance than those with chronic infection (odds ratio [OR], 1.640, p = 0.034; OR, 1.664, p  =  0.032; OR, 1.636, p  =  0.040; and OR, 2.601, p  =  0.012, respectively). Multivariate logistic regression analysis showed that KIR2DL5A–/2DL5B+ associated with HCV clearance (OR, 2.448, p  =  0.027), independent of sex, IL28B, and other KIRs . In contrast, KIR2DL3/2DL3 (OR,  0.610, p  =  0.034) as well as 2DL3/2DL3 +HLA‐C1 or C1C1 (OR, 0.580, p  =  0.017; and OR, 0.639, p  =  0.025, respectively) was found associated with chronic HCV infection. The presence of the homozygous KIR2DL3 with or without its HLA ligand increased the OR of developing chronic HCV infection in the context of IL28B . CONCLUSIONS: In this study we identified KIR2DL5A–/2DL5B+ associated with HCV spontaneous clearance, while KIR2DL3/2DL3, 2DL3/2DL3 +HLA‐C1, or C1C1 associated with chronic infection. Our study highlighted the fact that the roles of KIR and KIR‐HLA contributed to the control of HCV infection by innate immune responses.